2023
DOI: 10.3847/1538-3881/acc2be
|View full text |Cite
|
Sign up to set email alerts
|

A Survey for High-redshift Gravitationally Lensed Quasars and Close Quasar Pairs. I. The Discoveries of an Intermediately Lensed Quasar and a Kiloparsec-scale Quasar Pair at z ∼ 5

Abstract: We present the first results from a new survey for high-redshift (z ≳ 5) gravitationally lensed quasars and close quasar pairs. We carry out candidate selection based on the colors and shapes of objects in public imaging surveys, then conduct follow-up observations to confirm the nature of high-priority candidates. In this paper, we report the discoveries of J0025–0145 (z = 5.07), which we identify as an intermediately lensed quasar, and J2329–0522 (z = 4.85), which is a kiloparsec-scale close quasar pair. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…There have been many optical searches for quasar pairs in the high-redshift Universe, where tens of candidates have been identified (z > 1; e.g., [119][120][121][122][123]). Most recently, two of the highest-z dual AGN candidates (z > 5) were detected via optical spectroscopy and photometry [124,125], and new observational techniques that leverage the angular resolution of Gaia have been effective first steps for detecting the dual AGN population at high-z (i.e., [126,127]). However, large surveys with wide-area coverage are necessary to find large samples of dual AGN candidates.…”
Section: Observations Of Dual Agns Via the Axis Agn Surveysmentioning
confidence: 99%
“…There have been many optical searches for quasar pairs in the high-redshift Universe, where tens of candidates have been identified (z > 1; e.g., [119][120][121][122][123]). Most recently, two of the highest-z dual AGN candidates (z > 5) were detected via optical spectroscopy and photometry [124,125], and new observational techniques that leverage the angular resolution of Gaia have been effective first steps for detecting the dual AGN population at high-z (i.e., [126,127]). However, large surveys with wide-area coverage are necessary to find large samples of dual AGN candidates.…”
Section: Observations Of Dual Agns Via the Axis Agn Surveysmentioning
confidence: 99%
“…One possible way to find these lensed quasars is to identify quasars with large apparent SMBH masses and Eddington ratios and carry out follow-up high-resolution imaging with HST or JWST. This method has been used in the discovery of the currently only known lensed quasar at z > 5 (Fan et al 2019) and provided promising lensed quasar candidates (Yue et al 2023).…”
Section: The Impact Of Lensing Magnification On Quasar Property Measu...mentioning
confidence: 99%
“…On the other hand, no pairs were found by Sandoval et al (2023) in their search from a large X-ray catalog at z ∼ 3. There are also projects to search for quasar pairs motivated by investigation of gravitational lensing (e.g., Richards et al 2006;Inada et al 2012;Yue et al 2023). From such a project based on the Dark Energy Survey (Abbott et al 2018), Yue et al (2021) found a candidate of quasar pair at z = 5.66, with a separation of 7.3 kpc.…”
Section: Introductionmentioning
confidence: 99%